2020
DOI: 10.1001/jama.2020.9843
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between N95 Extended Use and Reuse and Fit Failure in an Emergency Department

Abstract: The corresponding prevalence estimates for these 3 groups in 2018 were 3.7% (95% CI, 3.0%-4.6%), 7.9% (95% CI, 7.1%-8.6%), and 4.4% (95% CI, 3.7%-5.4%), respectively. The lowest prevalence of serious psychological distress among the subgroups examined in April 2020 was observed in adults aged 55 years or older (7.3% [95% CI, 4.8%-10.9%]). In April 2020, 13.8% (95% CI, 11.4%-16.6%) of US adults reported that they always or often felt lonely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 4 publications
4
84
1
Order By: Relevance
“…Probably the knowledge of the details on how to wear a mask correctly and the exercise on how to wear it in routine practice is still lacking. Our observation shows similar results to a quantitative t test compliance study in which 38.2% of subjects failed the test [9].…”
Section: Discussionsupporting
confidence: 89%
“…Probably the knowledge of the details on how to wear a mask correctly and the exercise on how to wear it in routine practice is still lacking. Our observation shows similar results to a quantitative t test compliance study in which 38.2% of subjects failed the test [9].…”
Section: Discussionsupporting
confidence: 89%
“…Probably the knowledge of the details on how to get worn a mask correctly and the exercise how to wear it in routine is still lacking. Our observation shows similar results to a quantitative fit test compliance study in which 38.2% of subjects failed the test [9].…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, at least one small study showed that, unsurprisingly, the reuse of N95 FFRs was associated with higher fit failure rate [ 106 ]. Thus, it is fundamental that the combination of disinfection and reuse are properly investigated, as the number of paired cycles that FFRs can be subjected to would most likely be lower than the number of disinfection cycles alone.…”
Section: Cautionary Notesmentioning
confidence: 99%